Oxidative and O2 diffusive function in triceps brachii of recreational to world class swimmers - Villanova, S.; Pastorio, E.; Pilotto, A. M.; Marciano, A.; Quaresima, V.; Adami, A.; Rossiter, H. B.; Cardinale, D. A.; Porcelli, S. (Experimental Physiology, 2025)
This study aimed to evaluate in vivo oxidative capacity and relative resistance to O2 diffusion using near-infrared spectroscopy (NIRS) in the m. triceps brachii of recreational to world class swimmers and evaluate their relationships with swimming performance. Twenty-eight swimmers were enrolled and assigned into three subgroups according to their level: `recreational/trained` (Tier 1/2; n = 8), `national` (Tier 3; n = 12) and `international/world class` (Tier 4/5; n = 8). Performance was evaluated by 100 m freestyle trials. Training volume was measured by self-reported distance (km/week). The recovery k of m. triceps brachii was non-invasively estimated by NIRS through repeated intermittent occlusions under two conditions: well-oxygenated (kHIGH) and low O2 availability (kLOW). The difference between kHIGH and kLOW (delta-k) was calculated as an index of relative resistance to O2 diffusion. FINA points and 100 m performance differed among all groups. Training volume was greater in Tier 4/5 (34.0 ± 5.5 km week-1) and Tier 3 (35.5 ± 11.6 km week-1) than in Tier 1/2 (6.4 ± 1.8 km week-1). kHIGH was greater in Tier 4/5 and Tier 3 (3.18 ± 0.41 and 2.79 ± 0.40 min-1) versus Tier 1/2 (2.10 ± 0.36 min-1; all P < 0.002). kHIGH correlated with FINA points, 100 m performance and training volume. delta-k was not different among tiers and was not associated with training volume or performance. M. triceps brachii oxidative capacity (kHIGH) was positively associated with performance and training volume in swimmers. delta-k, which reflects relative resistance to O2 diffusion, was not different among athletes. These data suggest that m. triceps brachii oxidative capacity is associated with swimming performance and that muscle O2 diffusing capacity exerts a similar relative resistance to O2 diffusive flow across swimmers.